50.5k views
3 votes
Help pleasseeeee ! 15 points

the answers are
(-1,-5)
(0,-3)
(4,5)
(9,15)

Help pleasseeeee ! 15 points the answers are (-1,-5) (0,-3) (4,5) (9,15)-example-1
User Marc Esher
by
5.8k points

2 Answers

6 votes

Answer:

Explanation:

Let's try to eliminate y.

First we multiply the first equation by 2,

4x - 2y = 6

x + 2y = -6

Then we add them together

5x = 0

x = 0

Now we plug x into the first equation,

4(0) - 2y = 6

-2y = 6

y= -3

Now we plug x into the second equation,

0 + 2y = -6

2y = -6

y = -3

So our answer is,

(0,-3)

User Bureaucoconut
by
5.9k points
3 votes

Answer:

(0,-3)

Explanation:

2x-y = 3

x+2y = -6

Multiply the first equation by 2 so we can eliminate y

2(2x-y =3)

4x -2y = 6

Add this to the second equation

4x -2y = 6

x+2y = -6

-----------------

5x +0y = 0

x = 0

Now find t

x+2y = -6

0+2y = -6

2y =-6

Divide by 2

y = -3

User RandyLahey
by
5.9k points